2017
DOI: 10.3987/com-16-s(s)25
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Properties of Azulene-Substituted Tetracyanobutadiene and Dicyanoquinodimethane Chromophores Connected with Naphthalene Cores

Abstract: Azulene-substituted tetracyanobutadienes (AzTCBDs) and dicyanoquinodimethanes (AzDCNQs) connected with naphthalene cores were prepared by the reaction of 1-azulenylalkynes with tetracyanoethylene (TCNE) and 7,7,8,8-tetracyanoquinodimethane (TCNQ) in a formal [2 + 2] cycloaddition-retroelectrocyclization. The characteristic intramolecular charge transfer (ICT) characters were investigated by using UV/Vis spectroscopy and theoretical calculation. The redox behaviors of AzTCBDs and AzDCNQs were examined by cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…UV/Vis of 1-AzTCBDs 29 and 30 with naphthalenec ores ( Figure 5) showed broad absorption bands at around 400-700 nm, arising from the ICT betweent he azulenea nd TCBD units. [48] Likewise, bis-1-AzTCBDs 31-34 also displayed broad absorption bands in the visible region, without ac lear peak maximai nt he region. Similart ot he bis-1-AzTCBDs 23-28,t he extinction coefficients of bis-1-AzTCBDs 31-34 increased in comparison to those of 1-AzTCBDs 29 and 30 as the number of 1-AzTCBD units on naphthalene ring increased.…”
Section: -Azulenyl Tcbds With Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 95%
See 2 more Smart Citations
“…UV/Vis of 1-AzTCBDs 29 and 30 with naphthalenec ores ( Figure 5) showed broad absorption bands at around 400-700 nm, arising from the ICT betweent he azulenea nd TCBD units. [48] Likewise, bis-1-AzTCBDs 31-34 also displayed broad absorption bands in the visible region, without ac lear peak maximai nt he region. Similart ot he bis-1-AzTCBDs 23-28,t he extinction coefficients of bis-1-AzTCBDs 31-34 increased in comparison to those of 1-AzTCBDs 29 and 30 as the number of 1-AzTCBD units on naphthalene ring increased.…”
Section: -Azulenyl Tcbds With Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 95%
“…[46] They also revealed their redox behaviors, which weren ot influenced by the number of TCBDu nits on the corannulene core. [48] Likewise, bis-1-AzTCBDs 31-34 also displayed broad absorption bands in the visible region, without ac lear peak maximai nt he region. [47] However,t he influence of the number and substitution positiono ft he TCBD units on pyrene on the spectroscopic and electrochemical properties were not investigated.…”
Section: -Azulenyl Tcbds With Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…and other research groups reported the synthesis of arylethynylazulenes 91 – 96 in 37–99% yield by Pd‐catalyzed cross coupling of the appropriate ethynylazulene with haloarenes or the inverse cross coupling reaction of the appropriate haloazulene with the corresponding ethynylbenzenes (Figure 14). [23,25,26,60–66] …”
Section: Reactions Of Ethynylazulenesmentioning
confidence: 99%
“…Bis(1‐azulenyl)naphthalene derivatives 138 – 141 [65] were also synthesized by Pd‐catalyzed alkynylation of iodoazulene 98 b with the corresponding diethynylnaphthalenes 137 (Scheme 30). [85] …”
Section: Reactions Of Ethynylazulenesmentioning
confidence: 99%